Defense and Security policies for the South Atlantic region - Neto, Manuel Domingos (Tensões Mundiais, 2018)
This paper resulted from a contribution presented during an event promoted by the Nationalities Observatory research group. In this occasion, I tried to discuss prevalent ideas in the academic analysis on International Relations and Defense Studies. My starting argument was that the extremely conservative literary production on these matters do not signalize to a conception of an autonomous and sovereign performance of the Brazilian State.